Affective Priming with Pictures of Emotional Scenes: The Role of Perceptual Similarity and Category Relatedness - Calvo, Manuel G.; Avero, Pedro (The Spanish Journal of Psychology, 2006)
Prime pictures portraying pleasant or unpleasant scenes were briefly presented (150-ms display; SOAs of 300 or 800 ms), followed by probe pictures either congruent or incongruent in emotional valence. In an evaluative decision task, participants responded whether the probe was emotionally positive or negative. Affective priming was reflected in shorter response latencies for congruent than for incongruent prime-probe pairs. Although this effect was enhanced by perceptual similarity between the prime and the probe, it also occurred for probes that were physically different, and the effect generalized across semantic categories (animals vs. people). It is concluded that affective priming is a genuine phenomenon, in that it occurs as a function of stimulus emotional content, in the absence of both perceptual similarity and semantic category relatedness between the prime and the probe.